Strategi Bisnis RSU PKU Muhammadiyah Blora Melalui Pemetaan Faktor Internal dan Eksternal - Lahdji, Aisyah (Universitas Muhammadiyah Semarang, 2015)
Business Strategy of PKU Muhammadiyah Blora Hospital through Mapping of Internal and External FactorsThe changing business environment demands hospital to adjust. the arrangement of strategic planning is required as of the hospital effort to answer the challenge off change. Therefore, the study highlighted in this research relates to the development of business strategy add the General Hospital of PKU Muhammediyah Blora. This research is an operational research conducted with descriptive approach on the service strategy planning in the public hospital (RSU) PKU Muhammadiyah Blora at the year 2016-2020. The result of this research direct the that RS PKU Muhammediyah Blora neat to develop service strategy planning. The developed service strategy planning refers to the result of focus group discussion (FGD) done in this research which had mapped out the strength and weakness owned by General Hospital of PKU Muhammadiyah Blora. The formulated service strategy planning include improving the quality of human resources through education and training programs, specialist scholarship programs for physicians, increasing partnership with specialist physician partners, adding capacity / number of beds, as well as improving service quality. the implementation of developed services strategy planning requires a commitment from all levels off staff in General Hospital of PKU Muhammadiyah Blora.